The zinc finger transcription factors Bbctf1α and Bbctf1β regulate the expression of genes involved in lipid degradation and contribute to stress tolerance and virulence in a fungal insect pathogen. Issue 8 (3rd March 2020) - Wang, Zheng‐Liang; Pan, Hai‐Bo; Huang, Jue; Yu, Xiao‐Ping
Abstract: BACKGROUND: To initiate insect infection, entomopathogenic fungi produce diverse cuticle‐degrading enzymes. Of those, lipolytic enzymes participate in epicuticular lipid hydrolysis and thus facilitate fungal penetration through the outermost cuticular barrier of the insect host. The Far/CTF1‐type zinc finger transcription factors play an important role in the regulation of lipolytic activity and fungal pathogenicity in plant pathogens but remain functionally unknown in fungal insect pathogens. RESULTS: Two Far/CTF1‐type transcription factor Bbctf1α and Bbctf1β, which are essential for differential expression of genes involved in the fungal lipid degradation, were identified and functionally characterized in a fungal entomopathogen Beauveria bassiana . Disruption of each gene led to drastic losses of extracellular lipolytic activities under lipidic substrate‐inducing conditions, followed by remarkable phenotypic defects associated with the fungal biocontrol potential. These defects mainly included severe impairments of mycelial growth and conidium formation, and drastic losses of tolerance to the stresses of oxidation and cell wall perturbation during colony growth under either normal or induction conditions. Bioassays showed that the virulence of each disruption mutant on the greater wax moth was remarkably attenuated in topical immersion. However, there was no significant difference in intrahemolymph injection when the cuticle penetration process was bypassed. CONCLUSIONS: Bbctf1α and Bbctf1β are multifunctional transcription factors that play vital roles in the regulation of fungal lipid utilization and contribute to the vegetative growth, sporulation capacity, environmental fitness and pest control potential in B. bassiana . © 2020 Society of Chemical Industry Abstract : Bbctf1α and Bbctf1β are multifunctional transcription factors that play vital roles in the regulation of fungal lipid utilization and contribute to the vegetative growth, sporulation capacity, environmental fitness and pest control potential in Beauveria bassiana . © 2020 Society of Chemical Industry